The scientists : a history of science told through the lives of its greatest inventors - Gribbin, John R. (Random House Trade Paperbacks, 2004)
Traces the development of science through the past five hundred years, focusing on the lives and achievements of individual scientists whose discoveries and research influenced the progression of science.